E-051 The Role of Follow-up Imaging after Resection of Brain Arteriovenous Malformations in the Pediatric Patient: A Review. (29th July 2016) - Jimenez, J; Gersey, Z; Wagner, J; Snelling, B; Ambekar, S; Peterson, E
Abstract : Object: Pediatric patients are at significant risk for recurrence of brain AVM after resection. While there is general consensus as to the importance of follow-up after surgical resection of an AVM, there is a lack of consistency in follow-up duration. The object of this systematic review is to examine the role of follow-up imaging in detecting AVM recurrence early and preventing AVM rupture. Methods: This systematic review was carried out with articles obtained through a search of the literature according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Results: Search results revealed 1052 articles, of which 13 studies describing 31 cases of AVM recurrence met criteria for inclusion in this study. Patients receiving follow-up imaging experienced AVM detection significantly earlier (mean = 3.56 years, SD = 3.67) than patients with no follow-up (mean = 8.86 years, SD = 5.61; p = 0.0085). While 13.34% of patients that were not receiving follow-up imaging presented with rupture of recurrent AVM, 57.14% of patients that were receiving follow-up imaging presented with ruptured recurrence (p = 0.019). Conclusions: Follow-up imaging has an integral role after AVM resection and is sometimes not carried out for a sufficient period of time, leading to delayed detection of recurrence and increased likelihood of recurrent AVM rupture. Disclosures: J. Jimenez: None. Z. Gersey: None. J. Wagner: None. B. Snelling: None. S. Ambekar: None. E. Peterson: None.